Analisis Content Influencer Gitasav Pada Statement â€œChildfreeâ€ Dalam Prespektif Islam - Puput Sapinatunajah; Tantan H ermansyah; Nasichah Nasichah (CV. ITTC INDONESIA, 2022)
YouTuber Gita Savitri Devi has been in the spotlight after publicly admitting that she and Paul Andre chose not to have children, aka childfree. Through Instagram and other social media to see the pros and cons response regarding the childfree statement. The form of Gitasav's statement in public will be in the spotlight for its fans and could influence it, where Gitasav's followers are dominated by the millennial generation. Referring to this background, this study aims to answer major and minor questions. The major question is, How is Gitasav Content Influencer Analysis on the Childfree Statement? And the content or research background of Gitasav was the first to state the childfree statement in public that it went viral? Then searching on the internet comes up regarding the childfree gitasav statement? What is the respons of audience research from the childfree statement by gitasav? In this study, the theoretical basis from Branston & Stanford was used in the research chapter. The research chapter explains which include: content or background research. Searching on the internet and audience research (Bronston & Stanford, 2003: 265-279). In an Islamic perspective, looking at childfree is something that is contrary to the concept of Islam. Which is that getting married and getting offspring is a concept of marriage. In the Qur'an this concept is contained in Surah Al-Imran:6. Indonesia is famous for its eastern culture which is full of tolerance. In Indonesia, where the majority of the population is Muslim, the childfree system of thought is very much against Islamic teachings. Childfree adherents assume that the presence of a child will be a burden on their life. Choosing childfree or not should consider the decision carefully not just following the existing trends. Keywords: Childfree, Gitasav, Islam and Indonesia Â Abstrak YouTuber Gita Savitri Â Devi menjadi sorotan usai secara terbuka mengakui bahwa dia dan Paul Andre memilih untuk tidak punya anak alias childfree. Melalui Instagram serta media sosial lainnya untuk melihat reson pro dan kontra terkait statement childfree. Bentuk pernyataan gitasav di publik akan menjadi sorotan bagi penggemarnya dan bisaÂ saja mempengaruhi, yang dimana followers gitasav di dominasi dari kalangan generasi milenial. Merujuk dari latar belakng tersebut, maka penelitian ini bertujuan untuk menjawab pertanyaan mayor dan minor. Pertanyaan mayor yaitu, Bagaimana Analisis Content Influencer Gitasav Pada Statement Childfree? Dan content or research background gitasav pertama kali menyatakanÂ statement childfree di publikÂ hingga viral? Lalu searching on the internet yang muncul terkait statement childfree gitasav? Apa respon audience research dari statement childfree oleh gitasav?Dalam penelitian tersebut menggunakan landasan teoritis dari Branston & Stanfford pada bab research. Pada bab research menjelaskan yang diantaranya: content or background research. Searching on the internet and audience research (Bronston & stanfford, 2003: 265-279). Dalam prespektif islam memandang childfree adalah suatu yang bertentangan dan konsep islam. Yang dimana bahwa menikah dan mendapatkan keturunan merupakan suatu konsep pernikahan. Dalam al-qurâ€™an konsep ini tertuang dalam surah al-imran ayat 6. Indonesia terkenal dengan budaya timur yang penuh toleransi. Di indonesia dengan mayoritas penduduknya beragama muslim sistem pemikiran childfree sangat bertentangan dengan ajaran islam. Bagi penganut childfree menganggap bahwa kehadiran seorang anak akan menjadi beban bagi kehidupannya. Memilih childfree atau tidak hendaknya mempertimbangkan keputusan dengan matang tidak hanya sedang mengikuti tren yang ada. Kata Kunci: Childfree, Gitasav, Islam Dan Indonesia Â